ISLAM AND THE QUESTION OF ITS COEXISTENCE WITH MODERN DEMOCRACY - Sofiandi, Sofiandi; Fauzi, Fauzi; Hassan, Alimuddin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Islam and Islamic culture are frequently discussed and debated around the world. These discussions have often been linked to immigration in general and assimilation and integration policies, and thus to the coexistence of different religious and ethnic groups, and to the practice of racism and racial segregation in particular. These issues have now become visible in cultural, religious and migration studies, as well as in studies of race relations and socio-economic inequalities. For example, people inside and outside academia question Islamic politics, the place of democracy and human rights in Islam, and most importantly, whether Islam can coexist with other (i.e. Western) cultures. Against this background, it is important to understand the Islamic cultural system, Islamic society and politics, including democracy, in Islam, Muslim views on migration and some other phenomena related to Islam. The article will discuss the norms and values of Islam in relation to current issues and the search for the place of political Islam, democracy in Islam and whether Islam can coexist with other cultures.